Does universalization of health work? Evidence from health systems restructuring and maternal and child health in Brazil - Sonia R. Bhalotra; Rudi Rocha; Rodigo R. Soares (University of Essex, Institute for Social and Economic Research (ISER), 2016)
We investigate restructuring of the health system in Brazil motivated to operationalize universal health coverage. Using administrative data from multiple sources and an event study approach that exploits the staggered rollout of programmatic changes across municipalities, we find large reductions in maternal, foetal, neonatal and postneonatal mortality, and fertility. We document increased prenatal care visits, hospital births and other maternal and child hospitalization, which suggest that the survival gains were supply-driven. We find no improvement in the quality of births, which may be explained by endogenous shifts in the composition of births towards higher-risk births.
Keywords: I12; I18; J10; J13; J24; O54; 330; family health program; health; primary care; inequality; access; Brazil